A look at social protection in Latin America against the pandemic - Aranha, Adriana; Bronzo, Carla (Brazilian Journal of Latin American Studies, 2021)
The article starts from the perspective that social protection is a central device to face inequalities and social risks, but its importance increases in the post-pandemic context of Covid19, demanding a paradigm shift and new representations and meanings for the role of the State in protecting the poorest and most vulnerable population. Starting from the description of typologies of social protection systems, it seeks to analyze the responses given by Latin American countries, in the field of non-contributory protection, to face the health crisis and its social implications. Based on secondary sources - national documents, reports from international agencies and articles on the subject - the article proposes a balance of the countries' initiatives in general, but with a focus on eight countries, representing countries with high, medium and low protection gaps: Brazil, Argentina, Chile, Uruguay, Peru, Ecuador, Bolivia and Paraguay. Based on the information collected for these countries, the article discusses some contemporary challenges in the context of social protection in Latin America. The conquest of citizenship, established as a desideratum in modern societies, faces structural barriers to be carried out in the region, the most unequal in the world.